Validation of New Care Coordination Quality Measures for Children with Medical Complexity - Parast, Layla (Acad Pediatr, 2018)
OBJECTIVES: To validate new caregiver-reported quality measures assessing care coordination services for children with medical complexity (CMC). METHODS: A cross sectional analysis of the associations between 20 newly developed Family Experiences with Coordination of Care (FECC) quality measures and three validation measures among 1209 caregivers who responded to a telephone or mailed survey between August-November 2013 in Minnesota and Washington. Validation measures included an access composite, a provider rating item, and a care coordination outcome measure, all derived from Consumer Assessments of Healthcare Providers and Systems (CAHPS(©)) survey items. Multivariate regression was used to examine associations between the three validation measures and each of the 20 FECC quality measures. RESULTS: Nineteen of the twenty FECC quality measures were significantly and positively associated with one or more of the validation measures. The components of care coordination demonstrating the strongest positive association with provider ratings included (1) having a care coordinator who was knowledgeable, supportive and advocated for the child’s needs (β =26.4; 95% Confidence Interval [CI] 20.0,32.8, scaled to reflect change associated with a 0 to 100 change in the FECC measure score) and (2) receiving a written visit summary that was useful and easy to understand (β =22.0; 95% CI 17.1,27.0). CONCLUSIONS: Nineteen newly developed FECC quality measures demonstrated convergent validity with previously validated CAHPS measures. These new measures are valid for assessing the quality of care coordination services provided to CMC and may be useful for evaluating new models of care focused on improving these services. WHAT’S NEW: We demonstrate the validity of newly developed caregiver-reported quality measures to assess care coordination services provided to children with medical complexity(CMC). These measures may be useful for assessing the quality of care coordination for CMC and identifying areas for improvement.